Phenotypic Spectrum and Molecular Basis in a Chinese Cohort of Osteogenesis Imperfecta With Mutations in Type I Collagen - Chen, Peikai; Tan, Zhijia; Shek, Hiu Tung; Zhang, Jia-nan; Zhou, Yapeng; Yin, Shijie; Dong, Zhongxin; Xu, Jichun; Qiu, Anmei; Dong, Lina; Gao, Bo; To, Michael Kai Tsun (Frontiers in Genetics, 2022)
Osteogenesis imperfecta (OI) is a rare inherited connective tissue dysplasia characterized with skeletal fragility, recurrent fractures and bone deformity, predominantly caused by mutations in the genes COL1A1 or COL1A2 that encode the chains of type I collagen. In the present study, clinical manifestations and genetic variants were analysed from 187 Chinese OI patients, majority of whom are of southern China origin. By targeted sequencing, 63 and 58 OI patients were found carrying mutations in COL1A1 and COL1A2 respectively, including 8 novel COL1A1 and 7 novel COL1A2 variants. We validated a novel splicing mutation in COL1A1. A diverse mutational and phenotypic spectrum was observed, coupling with the heterogeneity observed in the transcriptomic data derived from osteoblasts of 7 patients from our cohort. Missense mutations were significantly associated (χ2 p=0.0096) with a cluster of patients with more severe clinical phenotypes. Additionally, the severity of OI was more correlated with the quality of bones, rather than the bone mineral density. Bone density is most responsive to bisphosphonate treatment during the juvenile stage (10-15 years old). In contrast, height is not responsive to bisphosphonate treatment. Our findings expand the mutational spectrum of type I collagen genes and the genotype-phenotype correlation in Chinese OI patients. The observation of effective bisphosphonate treatment in an age-specific manner may help to improve OI patient management.